Use of the Community of Inquiry Framework to Measure Student and Facilitator Perceptions of Online Flipped Classroom Compared with Online Lecture Learning in Undergraduate Medical Education - Chang JJ; Hain A; Dosiou C; Gesundheit N (Advances in Medical Education and Practice, 2023)
Julia J Chang,1 Adam Hain,2 Chrysoula Dosiou,1,* Neil Gesundheit1,* 1Division of Endocrinology, Metabolism, and Gerontology, Department of Medicine, Stanford School of Medicine, Stanford, California; 2Office of Medical Education, Stanford School of Medicine, Stanford, California*These authors contributed equally to this workCorrespondence: Julia J Chang, Stanford School of Medicine, 300 Pasteur Dr., Room S025, Stanford, CA, 94305, Tel +1 650-724-2474, Fax +1 (248) 720-4461, Email jchang89@stanford.eduBackground: The COVID-19 pandemic and a movement away from traditional lecture-based learning have increased the use of online flipped classroom (FC) and active learning models in medical education. The Community of Inquiry (CoI) framework for online learning may be used to evaluate the effectiveness and strengths of the online FC model compared with other learning formats.Methods: An observational survey study was conducted to measure medical student and facilitator perceptions of an online FC endocrinology tutorial compared with online lecture experiences. For the tutorial, students were instructed to watch short, pre-recorded lecture videos on thyroid pathophysiology prior to class. During class, small groups of students were paired with a faculty facilitator in online Zoom rooms for case discussion. Students were surveyed using the CoI framework to assess elements of cognitive, social, and teaching presence between the two online learning modalities. Facilitators were also surveyed. Survey questions were rated on a 5-point Likert scale.Results: Fifty-three out of 92 students (58% response rate) and seven out of eight facilitators (88% response rate) completed surveys. In general, students felt that online FC learning improved cognitive, teaching, and social presence compared with online lecture. Areas of cognitive presence (mean score 3.9 ± 1.0 SD), such as stimulating curiosity and applying concepts, were highly rated. Certain elements of social presence (3.6 ± 0.9) and teaching presence (3.7 ± 0.9), such as expression of emotion and communication of expectations, garnered lower ratings. All surveyed facilitators felt that online FC was more effective and enjoyable to teach than online lectures but did not feel it was superior to in-person instruction.Conclusion: Medical students and facilitators viewed an online FC tutorial in endocrinology positively. Most, but not all, areas of the CoI framework were enhanced with the online FC tutorial compared with online lecture-based learning.Keywords: flipped classroom, online learning, community of inquiry, small group learning